2012 Cost Estimates of Establishing and Producing Papaya (Carica papaya) in South Florida - Edward A. Evans; Fredy H. Ballen; Jonathan H. Crane (EDIS)
With the recent spike in papaya prices due to phytosanitary restrictions on papayas from Mexico, many growers in South Florida are considering getting back into papaya production to target the ripe papaya market. Still, there are a lot of concerns as to whether the crop can be profitable in light of declining yields. Based on this discussion, the objective of this article is to provide needed information on the costs and returns associated with establishing and operating a five-acre papaya orchard in South Florida, and to assess the prices and yields that must be obtained to make a papaya orchard profitable. This 5-page fact sheet was written by Edward A. Evans, Fredy H. Ballen, and Jonathan H. Crane, and published by the UF Department of Food and Resource Economics, December 2012.